Knowledge, attitudes, and practice against COVID-19 in West Nusa Tenggara, Indonesia - Menap; Sismulyanto; Mursaka; Putra, Made Mahaguna (Universitas Airlangga, 2023)
Introduction: COVID-19 spread rapidly, but little is known regarding knowledge, attitudes, and practices (KAP) against COVID-19 among residents from various regions in Indonesia. This study aims to determine the level of knowledge, practice and attitudes related to COVID-19 to provide a scientific basis for the prevention and control of this major outbreak in Indonesia. Methods: Online survey with convenience sampling was conducted among urban and rural residents in West Nusa Tenggara Province, and collected 523 questionnaires through online media. The instruments used in this research are demographic information, such as age, gender, educational level, marital status and area of residence (urban or rural) and knowledge, attitude and practice questionnaires. Results: The results of multiple linear regression analysis showed that education level (p=0.01), gender (p=0.00) and age (p=0.03) had a significant effect on knowledge about COVID-19. Residential area (urban) affects practices related to COVID-19 (p=0.00). Furthermore, knowledge of COVID-19 (p=0.00) and area of residence (urban) (p=0.00) are closely related to residents' attitudes toward preventive measures that can control this disease. Conclusions: Both urban and rural residents of West Nusa Tenggara Province displayed moderate levels of knowledge as well as the practice of COVID-19 and showed the disease with a positive attitude. Developing suitable education programs targeted at the general residents in West Nusa Tenggara Province is essential to increase knowledge, attitudes, as well as practices of COVID-19, especially for rustic and low-educated citizens.